AUTOMATION OF THE PROCESS OF STUDYING CONFLICT SITUATIONS AND SOLVING GAME THEORY PROBLEMS WITH LINEAR PROGRAMMING METHODS - Кондратьєва, Наталія; Леонтьєва, Вікторія; Пазініч, Катерина; Желобецький, Арсеній; Усатенко, Геннадій; Горбачов, Олександр (SWorldJournal, 2025)
The research focuses on the automation of analyzing conflict situations through the effective solution of game theory problems. The article presents and substantiates a methodology for reducing mixed-strategy matrix games to linear programming problems. W